BENTUK PENYAJIAN TAMBUA TASA PADA PROSESI ARAK-ARAKAN PERNIKAHAN OLEH GRUP BACENANG ART DI LUBUK BASUNG - Randi Akbar, Randi Akbar; Hengki Armez Hidayat (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to determine the form of Tambua Tasa presentation in the wedding procession by the Bacenang Art Group in Lubuk Basung. This type of research is qualitative with a naturalistic method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data is collected through literature study, observation, interviews and documentation. The steps of data analysis are data collection, data reduction, data presentation and data triangulation. The results show that the form of Tambua Tasa presentation in the wedding procession by the Bacenang Art Group in Lubuk Basung consists of the wedding procession and elements of performance form. The Tambua Tasa presentation procession at a wedding celebration in Lubuk Basung begins with the preparation stage, followed by the groom's procession to the bride's house with Bacenang Art starting to form the parade line and Tambua Tasa players performing various energetic rhythm patterns with an increasing tempo. Once the bridal party arrives at the bride's house and the traditional welcoming ceremony is completed, the Bacenang Art Group performs the closing repertoire with a gradually slowing tempo. The elements of the performance consist of players, musical instruments, floor patterns, performance time and place, and the audience. The number of players in a single performance usually ranges from 7 to 11 people. The musical instruments used are Tambua and Tasa, talempong, Pupuik Tanduak, the costumes worn are guntiang cino clothes or traditional Minang silek attire, with galemobong trousers, and additional headbands such as deta. Tambua Tasa performances by the Bacenang Art Group are usually held in the afternoon before the akad ceremony and the audience for Tambua Tasa performances usually comes from various segments of society.